Lee wave generation rates in the deep ocean. Issue 7 (2nd April 2014) - Wright, Corwin J.; Scott, Robert B.; Ailliot, Pierre; Furnival, Darran
Abstract : Using the world's largest data set of in situ ocean current measurements, combined with a high‐resolution topography roughness data set, we use a model‐assisted hierarchical clustering methodology to estimate the global lee wave generation rate at the ocean floor. Our analysis suggests that internal wave generation contributes 0.75±0.19 TW (±2 standard deviation) to the oceanic energy budget but with a strong dependence on the Brunt‐Väisäla (buoyancy) frequency climatology used. This estimate is higher than previous calculations and suggests that internal wave generation may be a much more significant contributor to the global oceanic mechanical energy budget than had previously been assumed. Our results imply that lee wave generation and propagation may be a dominant sink of at least half and potentially the overwhelming majority of ocean surface wind work on the geostrophic circulation. Key Points: Internal wave generation may contribute 0.75±0.19 TW to oceanic energy budget This estimate is much higher than previous calculations Implies lee wave generation may be a dominant sink of wind work on surface